1999
DOI: 10.1128/jvi.73.9.7734-7744.1999
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus (SIV) from Sun-Tailed Monkeys (Cercopithecus solatus): Evidence for Host-Dependent Evolution of SIV within theC. lhoestiSuperspecies

Abstract: Recently we reported the characterization of simian immunodeficiency virus (SIVlhoest) from a central African l’hoest monkey (Cercopithecus lhoesti lhoesti) that revealed a distant relationship to SIV isolated from a mandrill (SIVmnd). The present report describes a novel SIV (SIVsun) isolated from a healthy, wild-caught sun-tailed monkey (Cercopithecus lhoesti solatus), another member of the l’hoest superspecies. SIVsun replicated in a variety of human T-cell lines and in peripheral blood mononuclear cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…SFVs are exogenous retroviruses enzootic in both New and Old World primates (16)(17)(18). Phylogenetic analyses of SFVs indicate a species-specific distribution of virus strains not unlike that of SIV among some African primate species (19)(20)(21)(22)(23). Among captive primate populations, seroprevalence of antibodies to SFV may reach 100% in adults, with many animals seroconverting before the onset of sexual maturity (19,24; J.…”
Section: Sfvmentioning
confidence: 99%
“…SFVs are exogenous retroviruses enzootic in both New and Old World primates (16)(17)(18). Phylogenetic analyses of SFVs indicate a species-specific distribution of virus strains not unlike that of SIV among some African primate species (19)(20)(21)(22)(23). Among captive primate populations, seroprevalence of antibodies to SFV may reach 100% in adults, with many animals seroconverting before the onset of sexual maturity (19,24; J.…”
Section: Sfvmentioning
confidence: 99%
“…Codivergence with host species over thousands or millions of years has often been invoked as the primary evolutionary mechanism shaping the diversity of many DNA (and some RNA) viruses (Beer et al 1999;Charrel et al 1999;Sugimoto et al 2002;Nemirov et al 2004). Importantly, inferences about key aspects of viral biology including the rate of evolutionary change in the viral genome and the timescale of speciation events, have often been made based on the assumption of host-virus codivergence, which automatically places the evolution of these viruses on the same scale as their hosts (Nakao et al 1997;Hughes and Friedman 2000;Sugimoto et al 2002;Nishimoto et al 2006;Krumbholz et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, phylogenetic analyses have elucidated the origins of HIV-1 and -2 epidemic (Gao et al, 1994(Gao et al, , 1999Korber et al, 2000;Lemey et al, 2003;Salemi et al, 2001;Sharp et al, 2000), the relationships of HIV to other simian lentiviruses Essex, 1994;Gao et al, 1992;Wertheim and Worobey, 2007), and the classification of HIV diversity within HIV-1 (Kosakovsky Pond et al, 2009). Cross-species transmissions Beer et al, 1999;Gao et al, 1999;Hahn et al, 2000;Plantier et al, 2009;Takehisa et al, 2009;Wertheim and Worobey, 2007;Worobey et al, 2004) have been identified and characterized through the use of phylogenetic approaches. Such methods have been used to test hypotheses of transmission events of HIV between individuals (Hillis and Huelsenbeck, 1994;Leitner et al, 1996;Xin et al, 1995), including their use as evidence of transmission in legal settings (Bernard et al, 2007;Crandall, 1995;Metzker et al, 2002;Ou et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetics has been key to the identification of drug-resistance mutational pathways (Buendia et al, 2009;Crandall et al, 1999) and the mechanisms of drug resistance (Carvajal-Rodríguez et al, 2008;Lemey et al, 2005a;Machado et al, 2009). Moreover, phylogenetic approaches have been used to assess within-and among-host HIV diversity and population dynamics (i.e., phylodyanamics) (Grenfell et al, 2004), co-divergence (Beer et al, 1999;Bibollet-Ruche et al, 2004;Chen et al, 1996;Wertheim and Worobey, 2007), and the role of recombination in the diversification process (Carvajal-Rodríguez et al, 2007;Jobes et al, 2006;Schlub et al, 2010). This exceptional diversity has been examined to infer geographical distribution and dispersion patterns Robbins et al, 2003) and thereby test hypotheses associated with molecular epidemiology (Holmes et al, 1995;Salemi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%